Stretchable and Compressible Supercapacitor with Polyaniline on Hydrogel Electrolyte. Issue 16 (7th December 2018) - Jia, Rui; Du, Hui; Zhang, Xiaodong; Chen, Zhaojun; Chen, Di
Abstract : Flexible and stretchable supercapacitors (SCs) possessing good flexibility, light-weight and portability are important power units for next generation flexible electronics. Herein, we fabricated high-performance stretchable and compressible SCs by in-situ polymerizing polyaniline (PANI) as electrode materials onto both surfaces of the polymer hydrogel electrolyte (PHE) composed of polyacrylic acid crosslinked with vinyl hybrid silica nanoparticles. The PHE-PANI based SCs exhibit excellent electrochemical properties with the areal capacitance of 131 mF/cm 2 and cycling stability of 83.7% after 5000 cycles. The devices show outstanding electrochemical performance under both stretching and compressing states. The areal capacitance retention reaches to 162% under 600% stretching and increases slightly under 80% compression strain. A LED lamp can be lit up by three SCs in series in both stretching and compression states. All these results confirm that the PHE-PANI based SC is a promising candidate for novel flexible electronics.